Fresh perspectives on multimodal argument reconstruction - Stöckl, Hartmut (Frontiers in Communication, 2024)
The present contribution exemplifies current models for argument reconstruction on an environmental protection print-ad, identifying deficits in the way the models account for multimodal argumentation. Based on this critical review, three general research perspectives are suggested for making argument reconstruction maximally multimodal: the reach and logic of semiotic modes, multimodal coherence, and genre-specific multimodal discourse structure.If plastic pollution harms humans/the environment, it should be stopped. Premise 2:Plastic pollution harms the body as much as the ocean. Claim (Incitive):Say no to plastic.